2022
DOI: 10.3390/app122110976
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, Textural, and Sensorial Characterization of Walnut Butter

Abstract: The rheological properties of six formulated walnut semi-solid pastes with 0.5, 1.5, and 2.0% w/w xanthan gum, maple syrup, and Jerusalem artichoke powder were characterized using the Mars 40 rheometer (Thermo Haake, Karlsruhe, Germany). The butter samples’ textural behavior and color parameters (CIE L*, a*, and b*) were analyzed. Sensory evaluation and consumer acceptance were also analyzed. Walnut kernels were roasted at an optimized temperature (120 °C) and time (30 min) and subsequently made into walnut bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Totlani and Chinnan (2007) revealed that the viscosity of peanut butter was directly proportional to the concentration of emulsifier added in the product. Similar results were reported by Leahu et al (2022). Antioxidant activity and hexanal content: Antioxidant activity refers to the ability of a substance to neutralize or inhibit harmful effects of reactive oxygen species and free radicals.…”
Section: Fig 1: Physicochemical Composition Of Walnut Buttersupporting
confidence: 80%
“…Totlani and Chinnan (2007) revealed that the viscosity of peanut butter was directly proportional to the concentration of emulsifier added in the product. Similar results were reported by Leahu et al (2022). Antioxidant activity and hexanal content: Antioxidant activity refers to the ability of a substance to neutralize or inhibit harmful effects of reactive oxygen species and free radicals.…”
Section: Fig 1: Physicochemical Composition Of Walnut Buttersupporting
confidence: 80%